36 SPM leavers are excited to be at UMP - Mohamad Hakimi, Kamarudin (2019)
A total of 36 SPM leavers along with five teachers from Sekolah Menengah Kebangsaan (SMK) Chiku 2, Gua Musang experienced the campus life in Universiti Malaysia Pahang (UMP) on 3 December 2019. This two-day and one-night programme provided them with the boost to create success and path to university. According to Zainuddin Yusof, the Principal of SMK Chiku 2, the programme was aimed to expose the students in choosing the right course in the institutes of higher learning (IHL) in line with their SPM results.